Large Lecture Transformation: Adopting Evidence-Based Practices to Increase Student Engagement and Performance in an Introductory Science Course. Issue 1 (15th February 2016) - Russell, Jae-eun; Van Horne, Sam; Ward, Adam S.; Bettis, E. Arthur; Sipola, Maija; Colombo, Mariana; Rocheford, Mary K.
ABSTRACT: This study investigated students' attitudes, engagement, satisfaction, and performance in Introduction to Environmental Science after it was transformed from a typical large lecture to a student-centered learning environment. The instructors of the course collaborated with the Office of Teaching, Learning & Technology and radically redesigned the course by adopting evidence-based pedagogical methods and instructional technology to offer a rich active learning environment. Students' engagement, satisfaction, and performance in the transformed course were compared to the students in the same course that was traditionally taught in a previous semester in order to measure the effect of the transformed course on student learning. Four self-reported surveys and a focus group interview were administered during the semester, and performance scores, prior learning data, and demographic information were collected at the end of the semester. The assessment results indicate that the students in the transformed course prepared for the class significantly more, engaged in the course significantly better, and were significantly more satisfied with the course than were the students in the traditional lecture-format course. Most of all, multiple linear regression indicates that the students in the transformed course earned, on average, about three-fourths of a letter grade higher on their final grade after controlling for cumulative grade point average. The students in the transformed course reported that online learning materials and frequent formative assessments using online quizzes were helpful in their learning, and they perceived the course was relevant to real-world applications that matter to their daily life.